2005
DOI: 10.1073/pnas.0503523102
|View full text |Cite
|
Sign up to set email alerts
|

Reading depends on writing, in Chinese

Abstract: Language development entails four fundamental and interactive abilities: listening, speaking, reading, and writing. Over the past four decades, a large body of evidence has indicated that reading acquisition is strongly associated with a child's listening skills, particularly the child's sensitivity to phonological structures of spoken language. Furthermore, it has been hypothesized that the close relationship between reading and listening is manifested universally across languages and that behavioral remediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
345
4
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(381 citation statements)
references
References 40 publications
23
345
4
3
Order By: Relevance
“…Importantly, much larger brain activation was found at a region in-between BA6, BA8, and BA9 in NCS. We termed this region as a premotor association area (PMA), which has been previously associated with visuo-spatial processing and various functions more closely related to cognitive than to motor processes in humans and nonhuman primates as well (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, much larger brain activation was found at a region in-between BA6, BA8, and BA9 in NCS. We termed this region as a premotor association area (PMA), which has been previously associated with visuo-spatial processing and various functions more closely related to cognitive than to motor processes in humans and nonhuman primates as well (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the strong involvement of visuopremotor association in NCS may be related to the experience of reading Chinese characters (15,28). A Chinese character is composed of strokes and subcharacters that are packed into a square configuration, possessing a high, nonlinear visual complexity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be a good predictor of reading speed in several languages, regardless of orthographical transparency (e.g., Georgiou, Parrila, & Papadopoulos, 2008;Tan et al, 2005). Previously, there have been no studies exploring the relationship of infant brain responses and RAN.…”
Section: Predicting Reading Until Adolescencementioning
confidence: 99%
“…writing previously presented characters from memory) differs in young children with high or low overall literacy skill in Hong Kong [Pak et al, 2005]. Another study found that skill in copying Chinese pseudocharacters was highly correlated with reading scores in children, even with phonological processing skills statistically controlled [Tan et al, 2005b]. A study of Chinese dyslexic children also found that writing and reading are highly correlated [Chan et al, 2006].…”
Section: Introductionmentioning
confidence: 99%